Słownictwo tematyczne w rejestrach percepty i ekspensy cechu piwowarskiego w Krakowie - Pałucka-Czerniak, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article has been devoted to the vocabulary found in the expenses and revenue register of the brewers’ guild in Cracow from the 1760s and 1770s. The analysis serves to expand the knowledge about the language of official documents, the specific language of guild documents and thematically-specialized vocabulary, mainly administrative, legal and economic one. The reference point for the observations is the analysis of the lexis used in the community’s guild protocols. Both types of documents contain vocabulary related to the subject of professional work, conducting financial business and to administrative and judicial matters. The content of the lexis is somewhat similar, but each thematic category in both types of sources contains a slightly different lexical composition, the saturation of genres differs as well. The study of one type of guild documents, even those considered to be the most representative and typical, does not allow for characterising the entire specificity of communication and the lexical richness of the communicative medium – i.e. the official language of a particular community.